PERMINTAAN DAGING AYAM RAS PEDAGING PADA RUMAH MAKAN DI KECAMATAN PARIGI KABUPATEN PARIGI MOUTONG - Afandi, Afandi; Mujayin, Yudi; Azim, Muhamad (FAPETKAN UNTAD, 2016)
Broiler is one of animal food sources which is widely used as an alternative meat that much preferred by various community because it has a variety of benefits when compared to other sources of animal food. Â Parigi District has several supermarkets and traditional markets that provide broiler meat for restaurant needs. This research aimed to determine the influencing factors of demand as well as broiler meat demand by restaurant consumers and restaurant itself in the District of Parigi. The research was conducted in September-November 2013. Sampling is applied with multilevel cluster sampling (incidental multistage sampling). The samples taken at 30 restaurants and 132 restaurant consumers and designed using the survey method. Analysis of data using descriptive analysis and multiple linear regression analysis. The results of the study showed that the average demand for broiler meat in the restaurant achieved 83.167 g or 83,2 kg/month and by restaurant consumers was 5,613 g/month or a total of 5,6 kg/month. Revenue of restaurant owners and the number of food consumers had positive effect on the broiler meat demand of restaurants in the District of Parigi Moutong. The price of meat food menu and others had negative influence on broiler meat demand by restaurant consumers, whereas the consumer income and the consumer spending per month had positive affected for broiler meat demand by restaurant consumers in the District of ParigiÂ Moutong.Keywords: broiler meat, demand, restaurant